EKSTRAKURIKULER JURNALISTIK DAN DESAIN GRAFIS SEBAGAI RUANG PRODUKSI BUDAYA DIGITAL SANTRI DI PESANTREN - Dian Rahmana Putri; Arham Selo; Andi Abdul Hamza (Pascasarjana Universitas Al-Qolam Malang, 2026)
The development of digital media has brought about changes in communication patterns, literacy culture, and da’wah practices within Islamic boarding schools. The emergence of social media and visual communication has prompted Islamic boarding schools to adapt to advancements in modern communication technology without neglecting the Islamic educational values that form their core identity. This study employs a literature review method using a descriptive qualitative approach. Data were obtained through a review of various scientific articles, books, and relevant studies related to digital literacy, participatory culture, digital media communication, visual da’wah, and pesantren education over the past five years. The findings of this study indicate that the development of digital media has transformed the role of santri from mere consumers of information to producers of digital media through journalism and graphic design activities within the pesantren environment. Extracurricular journalism activities play a role in strengthening the culture of literacy, critical thinking skills, communication ethics, and public communication skills among santri. Meanwhile, extracurricular graphic design activities serve as a space to develop visual da’wah and represent the digital identity of santri through the production of Islamic content on social media. On the other hand, the development of digital culture in Islamic boarding schools also presents challenges in the form of instant communication culture, low information verification skills, and issues of digital communication ethics. Therefore, strengthening digital literacy based on Islamic values is crucial to ensure that digital culture within the boarding school environment continues to develop in a critical, creative, and ethical manner.